Patterns of Cognitive Strengths and Weaknesses and Relationships to Math Errors. (February 2017) - Koriakin, Taylor; White, Erica; Breaux, Kristina C.; DeBiase, Emily; O'Brien, Rebecca; Howell, Meiko; Costa, Michael; Liu, Xiaochen; Pan, Xingyu; Courville, Troy
This study investigated cognitive patterns of strengths and weaknesses (PSW) and their relationship to patterns of math errors on the Kaufman Test of Educational Achievement (KTEA-3). Participants, ages 5 to 18, were selected from the KTEA-3 standardization sample if they met one of two PSW profiles: high crystallized ability (Gc) paired with low processing speed/long-term retrieval (Gs/Glr; n = 375) or high Gs/Glr paired with low Gc ( n = 309). Estimates of Gc and Gs/Glr were based on five KTEA-3 subtests that measure either Gc (e.g., Listening Comprehension) or Gs/Glr (e.g., Object Naming Facility). The two groups were then compared on math error factors. Significant differences favored the High-Gc group for factors that measure math calculation, basic math concepts, and complex computation. However, the two groups did not differ in their errors on factors that measure geometry/measurement or simple addition. Results indicated that students with different PSW profiles also differed in the kinds of errors they made on math tests.